Research on Planning Plant-Pattern and Water Gates Operational Pattern of Swamp Reclamation Network on Rimau Island in Kabupaten Musi Banyuasin of South Sumatera - Wirosoedarmo, Ruslan; Apriadi, Usman (Fakultas Teknologi Pertanian Universitas Brawijaya, 2002)
Research uses descriptive approach comprises to climate assessment, rainfall, landscape, topography, hydro topography, reclamation network technical data, and farming entrepreneur data in field. The data are analyzed to ensure that planting pattern and operational pattern of water gate is suited with farming demand. Result indicated that water management network in researched area is less than expected. Planting pattern is only for once planting season a year (Paddy-Bera), while the plan is for three times a year (Paddy-Paddy-Palawija). Maximum demand of water obtained by second period in month of October equals to 261,35 mm/period or 17,42 mm/day. Operational pattern of secondary and tertiary water gates of rice field during wet season is focused for retention, controlling drainage to waste excessive rainfall or during fertilization, rinsing and washing off toward toxic and acid materials, and rise-down tide irrigation. Drainage is demanded when water is inundated too deep or water quality gets worst. Palawija is planted at dry season, that is, after second cropping of rice is finished and extended to drainage. Analysis result indicates that planting pattern of researched area (Paddy-Bera) is predicted to Rp.1.495.000/ha/year and that planting-planned pattern (Paddy-Paddy-Palawija) is estimated to Rp. 7.730.750/ha/year. Â Keywords: Planning Plant-Pattern, water management network, swamp reclamation